Preparation method of Cr / Ta double-layer coating with double metallurgical bonding in barrel inner bore
By forming a Cr/Ta double-layer coating on the inner chamber of the artillery body, using ion plating and high-power pulse magnetron sputtering technology, environmental pollution caused by hexavalent chromium plating in the prior art and poor coating performance are solved. Problem, efficient ablation protection and long-life coating performance are achieved.
Patent Information
- Application Number
- CN202310113328.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-02-15
AI Technical Summary
The existing artillery body barrel protection process relies on hexavalent chromium electroplating, resulting in environmental pollution and poor coating performance, especially in extreme environments that are prone to peel off and fail prematurely.
The Cr base layer is deposited by ion plating process, and the Ta surface layer is deposited by high-power pulse magnetron sputtering process to form a Cr/Ta double-layer coating to ensure that the two interfaces of Fe/Cr and Cr/Ta form a metallurgical bond.
The metallurgical integration of the Cr/Ta double-layer coating is achieved, which improves the service time and ablation life of the coating, and avoids environmental pollution and performance defects of hexavalent electroplating.
Smart Images

Figure HDA0004077651870000011 
Figure HDA0004077651870000012
Abstract
Description
Technical field:
[0001] The invention relates to the field of material science and technology, and in particular to a method for preparing a Cr / Ta double-layer coating with double metallurgical bonding in a barrel inner bore. Background technology:
[0002] At present, the protection of the inner bore of artillery barrels at home and abroad still mainly relies on the hexavalent chromium electroplating process, which seriously pollutes the environment. Although the waste liquid after plating is treated in an environmentally friendly way, the discharged waste liquid still causes a certain degree of pollution to the environment, the related ions cannot be degraded and the eco-friendliness is poor.
[0003] Therefore, research on magnetron sputtering of tantalum has begun both at home and abroad. Among them, the research of the Benet Laboratory in the United States is more engineering and systematic, and some research results have been announced. In related research (48th Annual Technical Conference Proceedings (2005), 511-518), it was found that in the case of 4 closed explosives in service, large-scale peeling occurred between the coating and the substrate, and the coating performance was poor. In addition, Ellis et al. (Acta Mater. 150 (2018) 317-326) found that at low temperatures, due to the gas absorption characteristics of tantalum, it can capture oxygen during the sputtering process, thereby forming a tantalum oxide base layer, and based on this epitaxial growth, a β brittle crystal phase is obtained, which will greatly affect the toughness of the coating. Under the interaction of force / heat / chemistry during the launch of the shell, the Ta coating will quickly peel off near the interface, thereby failing prematurely.
[0004] During the service process, we hope to combine the good compatibility of Cr with the matrix, high interface matching, high wear resistance and the high ablation resistance, high corrosion resistance, high hardness and high plasticity of α-Ta to resist the extreme environment of the barrel inner bore. Therefore, the present invention develops a double-layer coating with ion-plated Cr as the bottom layer and high-power pulsed magnetron sputtering Ta as the surface layer to solve the above problems. Summary of the invention:
[0005] The purpose of the present invention is to provide a method for preparing a Cr / Ta double-layer coating with double metallurgical bonding in the inner bore of a barrel, so that both the Fe / Cr and Cr / Ta double interfaces form metallurgical bonding.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a Cr / Ta double-layer coating with double metallurgical bonding on the inner bore of a barrel. The method comprises depositing a Cr base layer and a Ta surface layer in sequence on the surface of the inner bore of the barrel, and forming metallurgical bonding at the interface between the substrate and the Cr base layer (Fe / Cr) and between the Cr base layer and the Ta surface layer (Cr / Ta).
[0008] The method specifically comprises the following steps:
[0009] (1) An ion plating process is used, the target material is a pure chromium column target, and a Cr base layer is deposited on the substrate; the arc current is 80 to 150A, the substrate negative bias voltage is -600 to -1000V, the duty cycle is 50 to 60%, and high-purity Ar gas is filled to a vacuum degree of 0.2 to 3Pa for 10 to 30 minutes.
[0010] (2) An ion plating process is used, the target material is a pure chromium column target, and the Cr base layer is continuously deposited after adjusting the process parameters; wherein the arc current is 80 to 150 A, the substrate negative bias voltage is -80 to -200 V, the duty cycle is 20 to 80%, and high-purity Ar gas is filled to a vacuum degree of 0.1 to 0.5 Pa for 30 to 120 min.
[0011] (3) A high-power pulsed magnetron sputtering process is adopted, wherein the target material is a pure tantalum column target, and a Ta surface layer is deposited on the Cr base layer obtained in step (2); wherein the target discharge voltage is 400-800 V, the pulse width is 30-100 μs, the peak current is 200-800 A, the peak voltage is 600-1000 V, the substrate negative bias voltage is -800--1000 V, the duty cycle is 50-60%, and high-purity Ar gas is filled to a vacuum degree of 0.2-3 Pa for 10-120 min.
[0012] (4) A high-power pulsed magnetron sputtering process is used, the target material is a pure tantalum column target, and the Ta surface layer is deposited after adjusting the process parameters; the target discharge voltage is 400-800V, the pulse width is 30-100μs, the peak current is 200-800A, the peak voltage is 600-1000V, the substrate negative bias voltage is -20--200V, the duty cycle is 20-80%, and high-purity Ar gas is filled to a vacuum degree of 0.2-0.5Pa for 60-480min.
[0013] The method of the present invention obtains a Cr / Ta double-layer coating on the inner bore substrate of the barrel, and the obtained deposited coating does not require subsequent heat treatment and does not affect the mechanical properties of the self-tightening barrel.
[0014] During the deposition process of the method of the present invention, the overall temperature of the barrel is maintained between 200 and 300°C.
[0015] The difference between the inner diameter of the barrel and the diameter of the target is between 50 and 80 mm.
[0016] In the Cr / Ta double-layer coating, the interface between the substrate and the Cr base layer (Fe / Cr interface) has an interdiffusion zone of more than 2 microns, and the interface between the Cr base layer and the Ta surface layer (Cr / Ta interface) forms an interdiffusion zone of more than 0.4 microns.
[0017] The advantages and beneficial effects of the present invention are:
[0018] 1. In the Cr / Ta double-layer coating obtained by the present invention, the Ta coating is a body-centered cubic α phase, and the Cr base layer is obtained in the inner bore of the barrel by an ion plating process, and forms a metallurgical bond with the substrate at a low temperature without cracks. In addition, the Cr material itself does not have the air-intake property, so there is no basic condition for the epitaxial nucleation of the β phase, so the obtained Ta surface layer is 100% α phase.
[0019] 2. Under the implementation of high-power pulsed magnetron sputtering process, the Ta surface layer also forms a metallurgical bond with the Cr transition layer without cracks, so that the substrate / Cr / Ta forms a metallurgical whole, which greatly improves the service life of the coating, and thus the ablation life of the inner bore of the barrel is also greatly improved. Description of the drawings:
[0020] Figure 1 Cross-sectional morphology of Cr / Ta double-layer coating on PCrNi3MoVA steel surface.
[0021] Figure 2 This is the EDS energy spectrum line scan across the Fe / Cr / Ta double interface. Specific implementation method:
[0022] The present invention is further described in detail below by way of examples.
[0023] Example 1
[0024] The substrate is made of 30CrNi3MoV alloy steel, the sample size is 15mm×10mm×2mm, the distance between the substrate and the target is 50mm, and the substrate is loaded into the working room after sandblasting and surface ultrasonic cleaning; the working room is evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the area around the sample to 200 degrees Celsius, and then evacuate the background vacuum to 1×10 -2 Pa. Ion plating was used, the target material was a pure chromium column target, and high-purity Ar gas was filled to a vacuum degree of 3Pa, with an arc current of 100A, a substrate negative bias voltage of -800V, a duty cycle of 60%, and a deposition time of 20min. Then the substrate negative bias voltage was changed to -80V, the duty cycle was 80%, and high-purity Ar gas was filled to a vacuum degree of 0.14Pa, and the deposition time was 60min. Then the furnace was cooled to room temperature under vacuum and taken out of the furnace. Then a pure tantalum column target was installed, and the working chamber was evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the area around the sample to 200 degrees Celsius, and then evacuate the background vacuum to 5×10 -3Pa. High-power pulsed magnetron sputtering process was used for coating, in which the target discharge voltage was 800V, the pulse width was 30μs, the peak current was 260A, the peak voltage was 1000V, the substrate negative bias was -900V, the duty cycle was 60%, high-purity Ar gas was filled to a vacuum degree of 0.4Pa, and the deposition time was 40min. Then the substrate negative bias was changed to -120V, the duty cycle was 30%, and the deposition time was 420min. Finally, it was cooled to room temperature in the vacuum furnace and taken out of the furnace.
[0025] The cross-section of the Cr / Ta coating after deposition is observed, such as Figure 1 As shown in the figure, it can be seen that the film structure is dense, the Fe / Cr and Cr / Ta interfaces are well bonded, and no shielding holes appear. The energy spectrum element line scan is performed on the Fe / Cr / Ta double interface, and the element distribution results are as follows Figure 2 It can be clearly seen that the Fe / Cr interface forms an interdiffusion zone of nearly 4 microns, and the Cr / Ta interface forms an interdiffusion zone of 1 micron. The double-layer coating forms an integrated relationship with the substrate, and the coating bonding strength is greatly improved.
[0026] Example 2
[0027] The substrate is made of 30CrNi3MoV alloy steel, the sample size is 15mm×10mm×2mm, the distance between the substrate and the target is 30mm, and the substrate is loaded into the working room after sandblasting and surface ultrasonic cleaning; the working room is evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the sample to 300 degrees Celsius, and then evacuate the background vacuum to 7×10 -3 Pa. Ion plating was used, the target material was a pure chromium column target, and high-purity Ar gas was filled to a vacuum degree of 0.5Pa. The arc current was 80A, the substrate negative bias voltage was -900V, the duty cycle was 60%, and the deposition time was 30min. Then the substrate negative bias voltage was changed to -100V, the duty cycle was 50%, and high-purity Ar gas was filled to a vacuum degree of 0.2Pa, and the deposition time was 90min. Then the furnace was cooled to room temperature under vacuum and taken out of the furnace. Then a pure tantalum column target was installed, and the vacuum chamber was evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the sample to 300 degrees Celsius, and then evacuate the background vacuum to 5×10 -3 Pa. High-power pulsed magnetron sputtering process was used for coating, in which the target discharge voltage was 850V, the pulse width was 50μs, the peak current was 280A, the peak voltage was 1000V, the substrate negative bias was -980V, the duty cycle was 70%, high-purity Ar gas was filled to a vacuum degree of 0.3Pa, and the deposition time was 40min. Then the substrate negative bias was changed to -100V, the duty cycle was 80%, and the deposition time was 300min. Finally, it was cooled to room temperature in the vacuum furnace and taken out of the furnace.
[0028] The cross-section observation of the Cr / Ta coating after deposition shows that the film structure is dense, the Fe / Cr and Cr / Ta interfaces are well bonded, and no shielding holes appear. The energy spectrum element line scan of the Fe / Cr / Ta double interface shows that a nearly 6-micron interdiffusion zone is formed at the Fe / Cr interface, and a 1.2-micron interdiffusion zone is formed at the Cr / Ta interface. The double-layer coating forms an integrated relationship with the substrate, and the coating bonding force is greatly improved.
[0029] Example 3
[0030] The substrate is made of 30CrNi3MoV alloy steel, the sample size is 30mm×20mm×4mm, the distance between the substrate and the target is 40mm, and the substrate is loaded into the working room after sandblasting and surface ultrasonic cleaning; the working room is evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the sample to 150 degrees Celsius, and then evacuate the background vacuum to 8×10 -3 Pa. Ion plating was used, the target material was a pure chromium column target, and high-purity Ar gas was filled to a vacuum degree of 1Pa, with an arc current of 150A, a substrate negative bias voltage of -1000V, a duty cycle of 60%, and a deposition time of 10min. Then the substrate negative bias voltage was changed to -150V, the duty cycle was 80%, and high-purity Ar gas was filled to a vacuum degree of 0.4Pa, and the deposition time was 40min. Then the furnace was cooled to room temperature under vacuum and taken out of the furnace. Then a pure tantalum column target was installed, and the vacuum chamber was evacuated to a pressure below 7×10 -2 Pa, turn on the heater to heat the sample to 250 degrees Celsius, and then evacuate the background vacuum to 5×10 -3 Pa. High-power pulsed magnetron sputtering process was used for coating, in which the target discharge voltage was 700V, the pulse width was 60μs, the peak current was 220A, the peak voltage was 950V, the substrate negative bias was -950V, the duty cycle was 60%, high-purity Ar gas was filled to a vacuum degree of 2Pa, and the deposition time was 20min. Then the substrate negative bias was changed to -100V, the duty cycle was 80%, and the deposition time was 180min. Finally, it was cooled to room temperature in the vacuum furnace and taken out of the furnace.
[0031] The cross-section observation of the Cr / Ta coating after deposition shows that the film structure is dense, the Fe / Cr and Cr / Ta interfaces are well bonded, and no shielding holes appear. The energy spectrum element line scan of the Fe / Cr / Ta double interface shows that a nearly 2-micron interdiffusion zone is formed at the Fe / Cr interface, and a 0.4-micron interdiffusion zone is formed at the Cr / Ta interface. The double-layer coating forms an integrated relationship with the substrate, and the coating bonding force is greatly improved.
[0032] In summary, in the Cr / Ta double-layer coating prepared by the method of the present invention, both the Fe / Cr and Cr / Ta double interfaces form a metallurgical bond, no subsequent heat treatment is required, and the mechanical properties of the self-tightening barrel are not affected. A gradient coating that matches the mechanical properties of the barrel material can be obtained on the barrel surface, while replacing the hexavalent electroplating crack chromium process. In addition, the Ta coating on the outer surface has the advantages of high ablation resistance, high corrosion resistance, and high wear resistance. At the same time, due to the sensitivity of Ta to oxygen, it is easy to obtain a β phase on the surface of oxygen-containing gun steel, and the formation of the Cr transition layer completely circumvents this weakness, and 100% of the α-Ta phase can be obtained. Therefore, the Cr / Ta can be used for ablation protection of the inner bore of medium and large caliber artillery barrels.
Claims
1. A method for preparing a Cr / Ta double-layer coating with double metallurgical bonding on the inner bore of a barrel, characterized in that: The method is to deposit a Cr base layer and a Ta surface layer on the inner surface of the barrel in sequence, and form metallurgical bonds between the substrate and the Cr base layer and between the Cr base layer and the Ta surface layer. The method comprises the following steps: (1) using an ion plating process, with the target material being a pure chromium column target, to deposit a Cr base layer on a substrate; The arc current is 80~150A, the substrate negative bias voltage is -600~-1000V, the duty cycle is 50~60%, high-purity Ar gas is filled to a vacuum degree of 0.2~3Pa, and the deposition time is 10~30min; (2) Using ion plating process, the target material is pure chromium column target, and the process parameters are adjusted to continue to deposit Cr as the bottom layer; the current is 80~150A, the substrate negative bias voltage is -80~-200V, the duty cycle is 20~80%, high-purity Ar gas is filled to a vacuum degree of 0.1~0.5Pa, and the deposition time is 30~120min; (3) using a high-power pulsed magnetron sputtering process, with a pure tantalum column target as the target material, to deposit a Ta surface layer on the Cr base layer obtained in step (2); wherein the target discharge voltage is 400-800 V, the pulse width is 30-100 μs, the peak current is 200-800 A, the peak voltage is 600-1000 V, the substrate negative bias voltage is -800--1000 V, the duty cycle is 50-60%, high-purity Ar gas is filled to a vacuum degree of 0.2-3 Pa, and the deposition time is 10-120 min; (4) A high-power pulsed magnetron sputtering process was used, with a pure tantalum column target as the target material. After adjusting the process parameters, the Ta surface layer was deposited. The target discharge voltage was 400-800 V, the pulse width was 30-100 μs, the peak current was 200-800 A, the peak voltage was 600-1000 V, the substrate negative bias was -20--200 V, the duty cycle was 20-80%, high-purity Ar gas was filled to a vacuum degree of 0.2-0.5 Pa, and the deposition time was 60-480 min. The Ta coating is a body-centered cubic α phase.
2. The method for preparing a double-metallurgically bonded Cr / Ta double-layer coating on the barrel inner bore according to claim 1, characterized in that: During the deposition process, the overall temperature of the barrel is maintained at 200~300℃.
3. The method for preparing the Cr / Ta double-layer coating with double metallurgical bonding in the barrel inner bore according to claim 1, characterized in that: The difference between the inner diameter of the barrel and the diameter of the target is 50~80mm.
4. The method for preparing a double-metallurgically bonded Cr / Ta double-layer coating on the barrel inner bore according to claim 1, characterized in that: The inner bore of the barrel is made of alloy steel.
5. The method for preparing a double-metallurgically bonded Cr / Ta double-layer coating on the barrel inner bore according to claim 1, characterized in that: In the Cr / Ta double-layer coating, the interface between the substrate and the Cr base layer has an interdiffusion zone of more than 2 microns, and the interface between the Cr base layer and the Ta surface layer forms an interdiffusion zone of more than 0.4 microns.
Citation Information
Patent Citations
Repairing method for cannon barrel inner chamber
CN104708267A
Magnetron sputtering device for inner cavity of pipe with large length-diameter ratio and method for preparing alpha-Ta coating
CN109735812A